Model Kepemimpinan Kepala Desa Panjalu Dalam Penerapan Kearifan Lokal Di Desa Panjalu Kecamatan Panjalu Kabupaten Ciamis - Ilham Maulana; Aan Anwar Sihabudin; Ii Sujai (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research aims to analyze the leadership model implemented by the Head of Panjalu Village in integrating local wisdom into village development policies and programs. The research method used is descriptive qualitative with an approach of in-depth interviews, participatory observation, and documentation studies. The results show that the leadership of the Head of Panjalu Village is not optimal in applying local wisdom. This is evidenced by several indicators, such as the lack of community participation in village programs and the minimal innovation carried out by the Head of Village. The community tends to be less involved in the development process, leading to the erosion of local values that should serve as guidelines in daily life. Therefore, this research recommends the need for a more effective and inclusive leadership model that can enhance community involvement and preserve local values. It is expected that the Head of Village can play a more active role in motivating the community to participate in village development, so that local wisdom can be well integrated into every aspect of community life.